Pengaruh Konsentrasi dan Lama Fermentasi Urin Sapi sebagai Pupuk Cair pada Pertumbuhan Bibit Karet (Hevea brasiliensis Muell. Arg.) - Vinda Nawang Sari; Made Same; Yonathan Parapasan (Politeknik Negeri Lampung, 2017)
The aims of this research is to get the best concentration of cow urine as liquid organic fertilizer on rubber seed growth, to get the best fermentation time for cow urine as liquid organic fertilizer on the growth of rubber seedlings, and get the best interaction between concentration and cow urine fermentation as liquid organic fertilizer on the growth of rubber seedlings. The experiment was conducted in teaching farm of State Polytechnic of Lampung from January 2016 until June 2016. The treatments arranged in Randomized Block Design (RBD) with the factorial pattern consisting of two factors. The first factor was the concentration of cow urine, consisting of four levels: 15 cc.l-1, 30 cc.l-1, 45 cc.l-1 and 60 cc.l-1. The second factor was the duration of cow urine fermentation, consisting of five levels: 0 day, 7 day, 14 day, 21 day and 28 day. Rubber seedlings were used as plant indicator. Observations included plant height, number of petiole, stem diameter, stem girth, and dry weight of biomass. The results showed that the treatment of cow urine concentration had significant effect on plant height and number of petiole, but very significant effect on stem diameter, stem girth and dry weight of biomass. Likewise, the treatment of cow urine fermentation has significant effect on all observed variables except on the dry weight of biomass has a very significant effect. The interaction between treatment of cow urine concentration and cow urine fermentation did not significantly affect all variables except on dry weight of biomass had significant effect, i.e. cow urine concentration treatment of 45 cc.l-1 and fermentation of cow urine for 28 days resulted in dry weight of biomass higher rubber seedlings.Â Â Keywords: cow urine, fermentation, rubber seedlingsPermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/651